2019
DOI: 10.18632/aging.102510
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-specific CAR-T cells trigger cell lysis in EGFR-positive TNBC

Abstract: Triple-negative breast cancer (TNBC) is an aggressive cancer subtype for which effective therapies are lacking. Epidermal growth factor receptor (EGFR) is overexpressed in various types of TNBC cells, and several EGFR-specific immunotherapies have been used to treat cancer patients. Chimeric antigen receptor engineered T (CAR-T) cells have also been used as cancer therapies. In this study, we generated two types of EGFR-specific CAR-modified T cells using lentiviral vectors with DNA sequences encoding the scFv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…Consistently with what we observed in vitro , EGFR CAR‐T cell treatment at three different dosages was capable of suppressing TNBC growth/metastasis in xenograft mouse models. A recent study reported that the third generation of EGFR CAR‐T cells effectively suppressed TNBC cell growth in vitro and tumorigenesis in vivo in models including TNBC patient‐derived xenografts 76 . We observed that a medium dose of CAR‐T cell treatment exhibited the best in vivo effect, which might be because of an optimal number of injected CAR‐T cells and amount of released cytokines.…”
Section: Discussionmentioning
confidence: 67%
“…Consistently with what we observed in vitro , EGFR CAR‐T cell treatment at three different dosages was capable of suppressing TNBC growth/metastasis in xenograft mouse models. A recent study reported that the third generation of EGFR CAR‐T cells effectively suppressed TNBC cell growth in vitro and tumorigenesis in vivo in models including TNBC patient‐derived xenografts 76 . We observed that a medium dose of CAR‐T cell treatment exhibited the best in vivo effect, which might be because of an optimal number of injected CAR‐T cells and amount of released cytokines.…”
Section: Discussionmentioning
confidence: 67%
“…EGFR is a receptor tyrosine kinase that mediates oncogenic signaling cascades which drive the growth, survival, and invasion of cancer cells (79). Approximately 45% -70% of TNBC patients overexpress EGFR and efforts to target this receptor in TNBC are well underway (74)…”
Section: Receptor Tyrosine Kinase Egfrmentioning
confidence: 99%
“…Chimeric antigen receptors (CARs) are synthetic receptors that when engineered into T cells can redirect them to tumor cell surface antigens, get activated to become cytolytic, and eventually eliminate targeted tumor cells (9,10). Various CARs can be generated by fusing the antigen-specific variable singlechain fragments with T cell activating and co-stimulatory signaling domains (11,12). Chimeric antigen receptor T (CAR-T) immunotherapy is an effective immunotherapy strategy and plays an important role in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%